Implementasi Kebijakan Perda Nomor 03 Tahun 2018 Tentang Pengelolaan Air Tanah di Dinas ESDM (Energi Sumber Daya Mineral) Provinsi Jateng - Muhammad Sofyan Gutama; Hardi Warsono (Journal of Public Policy and Management Review, 2019)
Groundwater management is a government effort to regulate and manage groundwater use in order to achieve sustainable and sustainable groundwater conservation. The use, licensing and exploitation of ground water is regulated to maintain the stability of sustainable ground water. This research further discusses the implementation of the Central Java Provincial Regulation No. 03 of 2018 regarding groundwater management in the ESDM (Energy Mineral Resources) Office of Central Java, Semarang City. This study uses descriptive qualitative research methods. This research attempts to describe the situation or event that refers to the phenomena of research on groundwater management in the use, licensing, and exploitation of groundwater and describes the factors that influence policy implementation according to the theory of George Edward III through several variables such as communication, resources, disposition, and bureaucratic structure. The results of the study explained that the implementation of the policies realized by the ESDM Service had taken place according to regulations. Factors considered to hinder the implementation of policies on groundwater management are lack of optimal licensing. Suggestions given by researchers from the results of research on groundwater management are the realization of coordination that is harmonious, harmonious and balanced so as to realize groundwater management in accordance with the principles of sustainability and sustainability.